ETIKA BERBELANJA ONLINE DI ERA TEKNOLOGI INFORMASI - Andry, Johanes Fernandes; Bernanda, Devi Yurisca; Lee, Francka Sakti; Deny, Deny; Mastan, Ignatius Adrian; Geasela, Yemima Monica (Jurnal Pengabdian dan Kewirausahaan, 2021)
The implementation of Community Service (PKM) activities in collaboration between the Child Friendly Integrated Public Space (RPTRA) Darma Suci and Department of Information Systems at Bunda Mulia University, Jakarta, with the theme Online Shopping Ethics in the Age of Information Technology with the sub-theme being an overview of e-business & e-commerce, types of e-commerce transactions, attitudes that buyers should have and online shopping trends during the pandemic. The target of this material is to be able to educate and provide understanding to participants on a form of electronic commerce (commonly called e-commerce) using electronic devices, either mobile phones or laptops. Most of the participants have already made e-commerce transactions, but many of the attitudes that buyers in online stores have to do that they don't know, such as how to make safe transactions, and find out the reputation of the seller are just being realized, and so on. receive great benefit from the material presented. Participants benefit greatly from the presentation of this training, it can be seen from their enthusiasm in asking questions with resource persons during the online presentation of the material. The questionnaire was given at the end of the presentation of the material, as feedback for the implementation of the event, the results obtained were positive both in terms of the results of the questionnaire questions for the material presented with an average score of 95.83%, as well as in terms of the results of the questions. questionnaire for resource persons with an average score of 97.5%